Effect of ketamine-midazolam / tiletamine-zolazepam protocols on physiological parameters in Chelonoidis carbonaria turtles subjected to routine exploratory procedures - González V., Roger (2022)
The aim of this study was to determine the effect of the ketamine-midazolam / tiletamine-zolazepam protocols on physiological parameters (respiratory rate, heart rate, partial oxygen saturation and central and peripheral temperature) in Chelonoidis carbonaria turtles subjected to routine exploratory procedures (swab rectal and buccal). Twenty turtles were randomly distributed into two groups: Group 1: ketamine + midazolam and Group 2: tiletamine + zolazepam intramuscularly. The results were evaluated according to time and treatment, as well as the time-treatment interaction. Significant differences were found between protocols for the variables of respiratory rate and heart rate (p<0.05), but not for the variables of partial oxygen saturation (Sp O2) and central and peripheral temperature (p>0.05).